A QUANTITATIVE CROSSWALK BETWEEN TOEFL ITP SCORES AND CEFR LEVELS: AN OUTCOME-BASED APPROACH FOR ELT IN HIGHER EDUCATION - Erna Nurkholida; Ulin Ni’mah Rodliya Ulfah; Rafidah Abdullah; Titik Setiasih (University of Kuningan, 2026)
As the Common European Framework of Reference for Languages (CEFR) gains prominence as a global benchmark, higher education institutions require precise and transparent methods to interpret institutional English proficiency test scores. However, the absence of empirical alignment between TOEFL ITP scores and CEFR levels poses challenges for outcome-based academic environments, particularly in relation to placement, certification, and policy decisions. This study aims to develop a quantitative crosswalk between TOEFL ITP scores and CEFR proficiency levels within an Outcome-Based Education (OBE) framework. Using a quantitative cross-sectional design, data were collected from 90 students in the seventh-semester university who completed a preparatory course and subsequently took an online TOEFL ITP prediction test via the institutional Learning Management System. The relationship between TOEFL ITP scores and CEFR classifications was analyzed using descriptive statistics, Pearson correlation, and linear regression. The findings reveal a strong and statistically significant positive correlation between TOEFL ITP scores and CEFR levels (r = .78, p < .001). Regression analysis indicates that CEFR levels explain 60.8% of the variance in TOEFL ITP scores (R² = .608), with an average increase of approximately 90 points per CEFR level. Most participants were classified at the B1 level, indicating an intermediate proficiency typical of students preparing for academic contexts. These findings provide empirical support for aligning TOEFL ITP scores with CEFR descriptors and highlight the potential of an outcome-based approach to enhance transparency, accountability, and curriculum-aligned assessment practices in English Language Teaching (ELT) in higher education.